2017
DOI: 10.1007/s13187-017-1240-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Primary Care Physicians Continuing Education Needs by Examining Clinical Practices, Attitudes, and Barriers to Screening Across Multiple Cancers

Abstract: Population-based cancer screening for cervical, breast, and colorectal cancers improves patient outcomes, yet screening rates remain low for some cancers. Despite studies investigating physician perceptions and practices for screening, many have focused on individual cancers and lack primary care physicians' (PCPs) realities around screening for multiple cancers. We surveyed 887 PCPs in British Columbia (BC) to examine practices, beliefs, barriers, and learning needs towards cancer screening across breast, cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…There were no participants from our study who indicated they ceased routine cancer screening due to results of IiP, which has been seen in interviews with other elective proactive genetic testing participants. 13 In contrast, 27.3% of surveyed participants with positive results did not accurately recall their results status, with actual test results ranging from low risk (heterozygous MUTYH ) to high risk ( BRCA2 ). This misinterpretation could have large implications for inaccurate cancer risk management.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There were no participants from our study who indicated they ceased routine cancer screening due to results of IiP, which has been seen in interviews with other elective proactive genetic testing participants. 13 In contrast, 27.3% of surveyed participants with positive results did not accurately recall their results status, with actual test results ranging from low risk (heterozygous MUTYH ) to high risk ( BRCA2 ). This misinterpretation could have large implications for inaccurate cancer risk management.…”
Section: Discussionmentioning
confidence: 95%
“…It can also reduce non-genetics healthcare providers’ reported genetic testing barriers of limited genetics knowledge, uncertainty with hereditary cancer testing criteria, and time limitations. 13 , 14 Previous research identified population genetic testing as an economically feasible way to identify high-risk hereditary cancer syndromes, given that costs for testing are low enough to outweigh the amount of the population that needs to be screened for impact. 15 , 16 Economic feasibility and the opportunity for intervention to reduce morbidity and mortality through increased screening or surgical interventions make hereditary cancer well suited to population screening given previously published principles.…”
Section: Introductionmentioning
confidence: 99%
“…We highlight this because supplemental screening is recommended for women at high breast cancer risk, 15,16,21,22,44,45 and dense breasts alone do not indicate high breast cancer risk 46 . The most frequently occurring response of additional screening likely reflects physicians’ preferences for more aggressive cancer screening, especially when faced with multiple guidelines 47‐49 . Whereas this recommendation is inconsistent with supplemental screening guidelines, it is consistent across physicians regardless of specialty or gender.…”
Section: Discussionmentioning
confidence: 99%
“…46 The most frequently occurring response of additional screening likely reflects physicians' preferences for more aggressive cancer screening, especially when faced with multiple guidelines. [47][48][49] Whereas this recommendation is inconsistent with supplemental screening guidelines, it is consistent across physicians regardless of specialty or gender. Physicians' clinical judgment may favor more aggressive screening; however, the potential for overdiagnosis and other negative outcomes associated with overscreening must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The results of that study suggested the need to improve awareness and adherence to screening guidelines and recommended practices. 8 …”
Section: Introductionmentioning
confidence: 99%